Prevalence of Thrombocytopenia Amongst Patients with Cirrhosis Presenting to Shaheed Saif Ur Rehman Government Hospital, Gilgit - Rehman, Zohaira; jan, Mahtab (Biological and Clinical Sciences Research Journal, 2025)
Thrombocytopenia is a common complication in patients with cirrhosis, often impacting clinical management. Understanding its frequency and associations can enhance early diagnosis and treatment strategies. Objective: To determine the frequency of thrombocytopenia among patients with cirrhosis and identify factors associated with its occurrence. Methods: A cross-sectional study was conducted after obtaining ethical approval from the Shaheed Saif-Ur-Rehman Government Teaching Hospital, Gilgit, and the CPSP (December 26, 2024, to March 26, 2025. The study included 190 patients who met the selection criteria, and written informed consent was obtained from each participant. Comprehensive physical and clinical examinations were performed, and a liver ultrasound was conducted to confirm cirrhosis. Blood samples were analyzed to assess platelet counts, with thrombocytopenia defined as a platelet count below 150,000 per cubic millimeter. A pre-designed proforma recorded demographic data, disease duration, and body mass index (BMI). Statistical analysis was performed using SPSS version 25. Results: The mean age of participants was 45.63±9.08 years, with 37.4% being above 50 years. Males represented 54.2% of the sample. The mean BMI was 26.87±3.56 kg/m², and the mean disease duration was 8.43±2.32 months. Urban residents comprised 60.0% of the sample. Monthly income distribution showed that 43.7% earned Rs. 40,000-80,000, and 35.8% earned less than Rs. 40,000. Most were from low socioeconomic backgrounds (52.1%), and 37.4% were illiterate. Thrombocytopenia was observed in 57.9% of patients, with a significant association found only with urban residence (p = 0.03). No significant associations were found with age, gender, income, or education. Conclusion: Thrombocytopenia is prevalent in more than half of cirrhotic patients, with a substantial association observed with urban residence. No significant links were found with age, gender, socioeconomic status, income, or education. Regular monitoring of platelet counts is crucial for the early detection and management of thrombocytopenia in cirrhotic patients. Further studies are needed to explore contributing factors and improve treatment strategies.